Colvin & Earle [compact disc]. - Colvin, Shawn; Earle, Steve (Fantasy, 2016)
Shawn Colvin and Steve Earl's debut self-titled album features six co-written original songs plus covers of songs made popular by such greats as the Rolling Stones and Emmylou Harris.